The German Länder - Reutter, Werner. author. aut Link
X, 107 p. 6 illus.
Keywords: The textbook looks at the German federal state from the perspective of the Länder. It provides information on the development of the German Länder, analyzes their significance for democracy, the federal state and the rule of law, and introduces the central principles of politics in the Länder. It offers those interested in politics, as well as teachers and students of political science, social science, law, and the humanities, a comprehensive as well as condensed overview of the German Länder. This book is a translation of the original German 1st edition, Die deutschen Länder by Werner Reutter, published by Springer Fachmedien Wiesbaden GmbH, part of Springer Nature in 2020. The translation was done with the help of artificial intelligence (machine translation by the service DeepL. com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. The Contents Introduction: The German Länder between diversity and unity The Länder: how they became what they are Federalism and Länder: basic constitutional principles and theories Representative and direct democracy in the Länder: Complement or contradiction? Parties and party systems in the Länder Parliaments, governments and constitutional courts: division of powers in the Länder The Länder, the Federation, and Europe The Länder, democracy, and federalism in Germany The Author Dr. Werner Reutter is a political scientist at the Humboldt University in Berlin.